Catalytic oxidation of dichloromethane over sol-gel oxides supported Pd or Ni - Leidy Marcela Martínez; Consuelo Montes (Revista Facultad de Ingeniería Universidad de Antioquia, 2004)
Several supported Pd or Ni catalysts were synthesized by the sol-gel method using ã-alumina, silica, sulfated zirconia and sulfated titania as carriers. The resulting catalysts were characterized by XRD and nitrogen adsorption, and evaluated in the catalytic oxidation of dichloromethane. The effect of different parameters were determined, i.e. method of synthesis, temperature and the type of support. The durability of the best catalyst (0,5% Pd impregnated over sulfated titania) was tested between 300 ºC and 350 ºC during 48 h. Under the conditions of this study, impregnated catalysts exhibited higher activity than those prepared by cogelation. Pd loaded catalysts showed higher conversion into CO2 and HCl. Catalyst activity also increased with increasing temperature. ã-Alumina and sulfated titania showed good activity but, the formation of CO is favored instead of CO2. Therefore, bifunctional catalysts, i.e. containing metallic and acid sites appear to be required for the decomposition of methylene chloride into CO2 and HCl.